A computational analysis of universal behavior of thermal groove in a moving grain boundary. (1st March 2022) - Verma, M.; Sugathan, S.; Bhattacharya, S.; Mukherjee, R.
Graphical abstract: Abstract: We report the existence of universal behavior of a mobile thermal groove in polycrystalline thin films using a novel three-dimensional phase-field model. The universal behavior is independent of film thickness, surface diffusivity and grain boundary mobility when grain boundary motion is in steady-state. Moreover, the simulated universal curve shows excellent agreement with Mullins' theory of mobile grooves for any groove shape. Onset of universality of surface profiles is concomitant with the attainment of steady-state motion of the grain boundary and a constant value of groove depth. On the other hand, in the case of thinner films, the interaction between the groove and the grain boundary leads to partial stagnation of the boundary. Even for grooves attached to decelerating boundaries we observe self-similarity of surface profiles, although this self-similar behavior is different from the ones associated with steady-state boundaries.